Dampak Pembelajaran Daring pada Siswa Kelas 5 SD Negeri Tegalrejo Khususnya pada Minat Baca Buku Cetak - Amaldi, Fitra (Prosiding University Research Colloquium, 2021)
This study aims to determine the impact of online learning on 5th grade students of SD Negeri Tegalrejo, especially on interest in reading printed books. This research applies a qualitative case study. Data were collected using a questionnaire from Google Form and semi-structured interviews. The sample used in this study were 15 parents of 5th grade elementary school students in Tegalrejo. The results of the research that has been conducted, show that online learning has an impact on 5th grade students of SDN Tegalrejo, especially on interest in reading printed book. It is proven by the results of the percentage of parental responses that have been processed in this study.